An Assessment of Cirebon’s Image As a Tourist Destination - Februadi, Agustinus; Djatnika, Tjetjep (KnE Social Sciences, 2020)
Cirebon has a variety of popular tourist attractions such as the Kasepuhan Palace for cultural / historical tourism, the tomb of Sunan Gunung Djati for religious tourism, the Batik Trusmi tourist area for shopping tourism, and many restaurants that provide local food for culinary tourism. As such, Cirebon has a diverse image as a tourist destination. But efforts to measure the image of Cirebon as a tourist destination empirically have never been undertaken. This research was conducted to fill the lack of empirical studies on the image of Cirebon as a tourist destination. This study uses a qualitative approach to provide opportunities for respondents to freely express their opinions. Data collection was conducted via semi-structured interviews of 400 domestic tourists. Data were processed by listing the words and calculated the percentage of frequency of occurrence. The results show that Cirebon is perceived as a destination for historical tourism, culinary and batik shopping. The respondents were found to feel happy, comfortable and enthusiastic when traveling to Cirebon. The palace (keraton), Sunyaragi cave and Batik Trusmi tourist areas are perceived as Cirebon’s unique destinations. Keywords: destination image, qualitative approach, culinary tourism, historical tourism